The Death Penalty for Terrorism Offenders in Indonesia: A Comparative Study of Criminal and Islamic Law - BJ, Abdul Muis; Baharudin, Baharudin (Hukum Keluarga Islam IAIN LANGSA, 2025)
This study presents a limited comparative analysis of Indonesian criminal law and Islamic law regarding the death penalty for acts of terrorism. The objective is to critically examine how the death penalty is regulated for individuals convicted of terrorism under both Indonesian criminal law and Islamic law, aiming to identify their similarities, differences, and implications for law enforcement. This normative legal research employs a comparative approach by analyzing legal texts, sources of fiqh and judicial interpretations, scholarly journals, and statutory laws related to the application of the death penalty. The findings reveal that, under Indonesian criminal law, the imposition of the death penalty for terrorism is governed by Law No. 5 of 2018 on the Eradication of Criminal Acts of Terrorism. In Islamic jurisprudence, terrorism is not explicitly discussed in traditional fiqh texts; however, it is often analogized to the concept of jarimah hirabah due to their similar characteristics. This analogy provides the legal and moral basis for imposing the death penalty on individuals convicted of terrorism. Both Islamic criminal law and Indonesia’s secular legal system categorize terrorism as an extraordinary crime that poses a serious threat to human safety, thereby justifying the potential use of the death penalty. Nevertheless, the two systems differ in their definitions of the crime’s legal elements. Islamic criminal law does not require that the consequences of the act be widespread, nor does it emphasize the perpetrator’s motive. In contrast, Indonesian criminal law stipulates that terrorism must involve widespread consequences to qualify under the statute. In addressing terrorism, the Indonesian government must carefully balance preventive measures with law enforcement actions. The death penalty should be regarded as a measure of last resort, applied with the utmost caution to ensure full compliance with human rights principles.